Development and polymorphism of simple sequence repeats (SSRs) in Kelampayan(Neolamarckia cadamba–Rubiaceae) using ISSR suppression PCR method - Seng-Loi, Phui; Wei-Seng, Ho; Shek-Ling, Pang; Julaihi, Abdullah (Scholars Research Library, 2014)
Simple sequence repeat (SSR) marker is a polymerase chain reaction (PCR)-based marker system which has become a marker of choice for understanding plant genetic diversity and a powerful tool in addressing genetic resources questions. However, the availability of SSR markers especially for forest tree species is limited thus far due to the high development cost, labour-intensive and time-consuming. The present study aimed to develop an array of SSR markers for Neolamarckia cadamba using inter-simple sequence repeat (ISSR) suppression PCR method and further assessed the polymorphisms and transferability of the markers to other species.In total, 15 out of 31 SSR markers specific for N.cadamba were successfully developed and further characterized and validated by using 30 individuals of N. cadamba. The markers exhibited a considerable high level of polymorphism across the tested N. cadamba genotypes whereby 66 alleles were detected with an average of four alleles per locus. Most of the SSRloci analyzed showed high polymorphism as indicated by their PIC value which was above 0.5. The most polymorphic lociwere: NCAC11 (PIC=0.849), NCAC12 (PIC=0.722) and NCAG01 (PIC=0.712).The transferability rate was ranging from 26.7% to 73.3% among the four cross-genera species tested. The present study is the first report on the development of SSR markers in N. cadamba. These markers provide valuable genomic resources that could pave the way for exploiting SSR genotype data for effective selection of plus trees, provenance trials and establishment of forest seed production areas (SPAs) of N. cadamba in the selected forest areas dedicated to planted forest development, and molecular breeding of N. cadamba and other indigenous tropical tree species in future.